Interview with What, artist, Katoomba, Australia, 8 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
What is an artist based in the Blue Mountains, a couple of hours west of Sydney, Australia. I first met What when we both worked at Campbelltown Arts Centre in 2001. I wrote the catalogue essay for What's Mothertrucker exhibition at Campbelltown in the same year, and we did a gallery talk at the National Art School Gallery in 2009. I regard What as one of Australia's most underrated contemporary artists, as well as one of the most varied and interesting artists I know. In this interview, What talks about his beginnings at the National Art School, and a number of his key exhibitions since.